Exchange Rate Equilibrium and Fundamentals in Asia-Pacific Countries - Ho, Catherine S. F.; Ariff, Mohamed (Asian Journal of Business and Accounting, 2008)
This paper provides new findings that extend the literature by investigating the time to equilibrium for price changes to catch up with exchange rate and the contribution of non-parity fundamentals in exchange-rate dynamics in a trade-related multi-country framework. It reports new findings on exchange behaviour by expanding the parity variables to include other theory-suggested variables with high and low-frequency multi-country panel regression analysis, and Divisia Index Model. Our findings indicate that exchange rates are affected by growth rates, capital and balanceof- payment flows, fiscal, monetary and other fundamentals. This study also confirms that long-run PPP equilibrium for a group of Asia Pacific countries is five years. These key findings are robust across different time intervals. Keywords: Exchange Rates, Parity Theorems, Trade and Capital Flows, Foreign Debt and Reserves, Growth, Monetary and Fiscal Policy JEL classifications: F31, F32, G15